Survey on the situation of using cephalosporin antibiotics in the treatment at the Department of Examination - Dam Doi General Hospital, Ca Mau province - To, HIếu Minh; To, Huỳnh Trâm; Le, Văn Út (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
In Vietnam, the management of using antibiotic in hospitals is one of the important activities in the management of pharmaceutics. Antibiotics use monitoring should be done to help identify potential risk of inappropriate antibiotic use. Survey on the status of cephalosporin antibiotic use during outpatient treatment at the Department of Examination - Dam Doi General Hospital, Ca Mau province. A cross-sectional descriptive study on 400 prescriptions of patients using cephalosporin antibiotics in the treatment at the Department of Examination - Dam Doi General Hospital, Ca Mau province from July 1, 2023 to October 31, 2023. The outpatient antibiotic utilization rate at Department of Medical Examination is 45.0%, with women having the highest usage (55.2%). Antibiotics are most commonly used in the 41-60 age range (31.3%), while the respiratory disease uses the most antibiotic (50.6%). Otorhinolaryngology has a high rate of antibiotic use (94%). There are no cases of combining three or more antibiotics in the same prescription, with 3rd generation cephalosporin being the most usually prescribed (60.0%). The general appropriate antibiotic usage rate was 98.9%. There are no prescriptions show antibiotic use for more than ten days. Cephalosporin was used for patients at the rate of 45%; the rate of rational use of antibiotics in outpatient prescriptions is 98,9%.